2017
DOI: 10.1016/j.maturitas.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and sarcopenia: A systematic review and meta-analysis

Abstract: Nicola.Inflammation and sarcopenia: A systematic review and meta-analysis.Maturitas http://dx.doi.org/10.1016/j.maturitas. 2016.11.006 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
408
2
16

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 567 publications
(443 citation statements)
references
References 38 publications
17
408
2
16
Order By: Relevance
“…However, it is not known whether these pathways could be directly applicable to the pediatric populations. In a meta‐analysis based on the data from adults, sarcopenia was found to be associated with higher levels of serum C‐creative protein, suggesting the role of inflammation in sarcopenia etiology . Children with diseases suffer some degree of inflammation, whether chronic or acute, which could be the hallmark features in childhood sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not known whether these pathways could be directly applicable to the pediatric populations. In a meta‐analysis based on the data from adults, sarcopenia was found to be associated with higher levels of serum C‐creative protein, suggesting the role of inflammation in sarcopenia etiology . Children with diseases suffer some degree of inflammation, whether chronic or acute, which could be the hallmark features in childhood sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis based on the data from adults, sarcopenia was found to be associated with higher levels of serum C-creative protein, suggesting the role of inflammation in sarcopenia etiology. 68 Children with diseases suffer some degree of inflammation, whether chronic or acute, which could be the hallmark features in childhood sarcopenia. Consideration of the alternative use of the term "myopenia" may be warranted but awaits further investigation related to the underlying changes in skeletal muscle morphology.…”
Section: Muscle Strength and Function In Childhoodmentioning
confidence: 99%
“…Batsis et al evaluated the prevalence of sarcopenia in the general population and observed an association between ALM adjusted for BMI and hsCRP levels [39]. In a recent systematic review and meta-analysys, Bano et al concluded that sarcopenia seems to be associated with elevated serum CRP levels, but no association was found with IL6 when compared to controls [40]. However, prospective studies with larger sample sizes involving the analysis of various inflammatory mediators will be necessary to elucidate the role of inflammation in sarcopenic CKD patients not yet on dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, weight loss has specifically been associated with increased circulating levels of TNFα in COPD (Di Francia et al ., Nov). In addition, sarcopenia is associated with high‐serum inflammatory parameters (Bano et al ., Feb), and a weak leg extension strength is related to high plasma TNF‐α in COPD (Ferrari et al ., ). It is likely that the slight difference in functional capacity/physical activity and the higher level of antioxidant capacity cannot counteract the effect of systemic inflammation on endothelial function in lean patients with COPD.…”
Section: Discussionmentioning
confidence: 99%